Pemberdayaan Orang Tua dan Edukasi terhadap Upaya Pencegahan Stunting Anak Usia 12-59 Bulan di Wilayah Kerja Puskesmas Pemancungan Padang - Oresti, Syalvia; Handiny, Febry (Universitas Alifah Padang, 2024)
Stunting is the impact of malnutrition that has accumulated over a long period of time and is an indication of a public health problem. This is associated with increased risk of morbidity and mortality, reduced physical capacity, retarded motor and mental development and function. The solutions that can be carried out in community service activities are as follows: Carrying out initial observations on the health of pregnant women, children and the community in the work area of ??Pemancungan Community Health Center, namely conducting a pre-test by observing and interviewing pregnant women, children and the community. Hold discussions with cadres and leaders of community health centers to plan and provide a place to provide health education. Providing health education and designing the process of implementing activities. The implementation method that will be carried out is through the preparation stages, common perception and delivery of an overview of the activity. This activity will be carried out from January 2024 with the target community specifically pregnant women and parents who have children aged 12-59 months. The evaluation was carried out by means of observation and qualitative data from pregnant women, children and the community in the working area of Pemancungan Community Health Center with the results that participants were able to explain the dangers of stunting. Based on the problems described, efforts were made to reduce the impact of inappropriate growth and development checks.